(untitled) (Proceedings of the International Conference on Education, 2023)
With the COVID-19 outbreak, many governments decided to ban any type of face-to-face teaching, disrupting classes and resulting in many students being unable to return to their institutions. Ensuring undisrupted learning when classes were disrupted needed the reform of the entire educational system to include an online education component. The impact of COVID-19 on remote teaching experiences of academic staff entailed increased workloads, balancing home and work life during the national lockdowns, concerns about students’ ability to participate in their studies, and at times feeling isolated. The objectives of this conceptual paper are to analyse the challenges faced by academic staff and students experienced in online learning, predict the changes in post-COVID-19 education, and propose measures against potential future outbreaks. The research tool used for analysing data gathered from different sources for this study was content analysis and the research method was descriptive research. The study was based on secondary data. Case studies of practices from higher education institutions in different countries are cited in the paper for benchmarking purposes. The paper argues that higher education teaching and learning innovations are needed to harness the technological tools used during the pandemic. The conceptual paper supplements the literature on resilient higher education systems in times of pandemics.